MRI monitoring of pathological changes in the spinal cord in patients with multiple sclerosis - Gass, Achim; Eisele, Philipp (The lancet, 2015)
The spinal cord is a clinically important site that is affected by pathological changes in most patients with multiple sclerosis; however, imaging of the spinal cord with conventional MRI can be difficult. Improvements in MRI provide a major advantage for spinal cord imaging, with better signal-to-noise ratio and improved spatial resolution. Through the use of multiplanar MRI, identification of diffuse and focal changes in the whole spinal cord is now routinely possible. Corroborated by related histopathological analyses, several new techniques, such as magnetisation transfer, diffusion tension imaging, functional MRI, and proton magnetic resonance spectroscopy, can detect non-focal, spinal cord pathological changes in patients with multiple sclerosis. Additionally, functional MRI can reveal changes in the response pattern to sensory stimulation in patients with multiple sclerosis. Through use of these techniques, findings of cord atrophy, intrinsic cord damage, and adaptation are shown to occur largely independently of focal spinal cord lesion load, which emphasises their relevance in depiction of the true burden of disease. Combinations of magnetisation transfer ratio or diffusion tension imaging indices with cord atrophy markers seem to be the most robust and meaningful biomarkers to monitor disease evolution in early multiple sclerosis.